How strong do global commodity prices influence domestic food prices in developing countries? A global price transmission and vulnerability mapping analysis - Matthias Kalkuhl (University of Bonn, Center for Development Research (ZEF), 2014)
This paper analyzes the transmission from global commodity to domestic food prices for a large set of countries. First, a theoretical model is developed to explain price transmission for different trade regimes. Drawing from the competitive storage model under rational expectations, it is shown that domestic prices can respond instantaneously to global prices even if no trade takes place but future trade is expected. Using a global database on food prices, we construct national and international grain price indices. With an autoregressive distributed lag model, we empirically detect countries in which food prices are influenced by global commodity prices, including futures prices. Mapping transmission elasticities with the size of the population below the poverty line which spends typically a large share of its income on food, we are able to estimate the size of vulnerable population. Our empirical analysis reveals that 90 percent of the global poor (income below 1.25/day) live in countries where domestic food prices respond to international prices - but the extent of transmission varies substantially. For 360 million poor people, international prices transmit to their country at rates of 30 percent or higher within three months.
Keywords: C22; E3; F1; F6; Q1; 330; time series econometrics; poverty; trade; storage; market integration; volatility; shocks; price indices